Application of Article 7 of the Rome II Regulation in the case of Begum v. Maran - Wydmański, Wojciech (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The subject of this article is an analysis of the English court’s consideration of the applicablelaw in Begum v. Maran. It concerned a claim against a multinational corporation for compensationfor the death of a shipyard worker in Bangladesh. The court in that case addressed the appropriatenessof using Article 7 of the Rome II Regulation, a special conflict of laws rule that determines the lawapplicable to environmental damage. The purpose of the paper is to show that the construction adoptedin Article 7 Rome II is favourable to persons injured by environmental pollution, however, the scope andinterpretation of this provision is narrowly applied. The paper will present the position of litigants andthe court, as well as the views presented in other decisions of English and EU courts and representativesof the doctrine of private international law.
Keywords: Environmental damage; Rome II Regulation; Article 7; Human rights